Meiotic chromosome behavior in Saccharum species, including the Brazilian variety SP80-3280 - Oliveira, Gleicy Kelly de (2022)
Modern cultivars of sugarcane (Saccharum spp.) are polyploids and accumulate aneuploidies as a result of domestication and their interspecific hybrid origin involving the domesticated species S. officinarum (\'noble cane\') and the wild S. spontaneum, both with an evolutionary history of polyploidy. Clones of S. officinarum (2n= 80) have been widely cultivated for their high sugar content but have proved susceptible to biotic and abiotic stresses. On the other hand, S. spontaneum has exhibited idiosyncratic behavior, such as adaptation to a variety of environmental conditions, high fiber content and resistance to crop diseases. For this reason, hybrids were backcrossed with S. officinarum in order to recover the sugar content produced by the noble canes. Selection of superior progenies in subsequent generations established the genetic basis for modern cultivars with a complex genome. Despite their hybrid, highly polyploid origin, classic studies of the meiosis of several cultivars have shown that pairing is predominantly bivalent. Our research group confirmed the occurrence of a bivalent association in Brazilian variety IACSP93-3046 using fluorescent in situ hybridization (FISH) with homologous probes in centromeric regions. For this thesis, we conducted a detailed study of meiosis in sugarcane based on two different approaches. The results of the first approach are given in chapter 1. A comparative analysis of the meiotic representatives of the parents, S. officinarum and S. spontaneum, and Brazilian variety SP80-3280 was run in pollen mother cells. Moreover, for the first time we identified and typified the occurrence of chromosomal inversions and dicentric chromosomes. Using FISH, we were able to determine how the chromosomal association in diakinesis was achieved, and in particular, the constitution of mitotic chromosomes in SP80-3280. In the second study, genomic in situ hybridization (GISH) was used to investigate the constitution of bivalent chromosomes in diakinesis, and also identify the origin of univalents and laggards during meiosis I and II in sugarcane cultivar SP80-3280. The data obtained herein suggests that there is coordinated chromosomal segregation, irrespective of origin, implying that meiotic pairing is under genetic control in Saccharum.